Potensi Bambu Sebagai Bahan Alternatif Untuk Furniture - I Gede Andika Permana Putra; Nyoman Trisnanda Suma Putra; Anak Agung Gede Raka Gunawarman; Ida Bagus Gede Parama Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Bamboo in Indonesia has close ties with the local community, especially in rural areas where bamboo is used in daily activities ranging from social to cultural, but bamboo is a material that is less popular in the eyes of people in urban areas to be used as furniture and other tools because of the stigma factor that bamboo is a cheap material, This study aims to find the advantages of bamboo as a natural material compared to wood. The advantages of bamboo are also found during the growth and harvest period compared to bamboo wood, which is much faster and bamboo has different types so that it has a variety of shapes and colors that make bamboo can be processed into more attractive products than wood.